To rewrite the equation \(3x + y = 7\) in slope-intercept form (which is \(y = mx + b\)), we can isolate \(y\):
-
Start with the original equation: \[3x + y = 7\]
-
Subtract \(3x\) from both sides: \[y = -3x + 7\]
Now we have \(y = -3x + 7\) in slope-intercept form.
Since both the original equation and the transformed equation represent the same line, the correct statement is:
The equation \(3x+y=7\) is \(y = -3x + 7\) in slope-intercept form, which means that statement #2 describes the system of equations.